Vein mechanism simulation study for deep vein thrombosis early diagnosis using cfd - Ibrahim N.; Abd Aziz N.S.; Abd Manap A.N. (Institute of Physics Publishing, 2023)
Blood; Blood vessels; Data visualization; Diagnosis; Diseases; Fluid mechanics; Hemodynamics; Orifices; Rotation; Velocity; Vorticity; CFD simulations; Deep vein thrombosis; Different sizes; Early diagnosis; Mechanism simulation; Pulmonary embolism; Rotational motion; Three parameters; Computational fluid dynamics